1996
DOI: 10.1093/ee/25.5.882
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Data-Based Analysis of Boll Weevil (Coleoptera: Curculionidae) Overwintering Survival and Spring Emergence

Abstract: Analysis of data from a 15-yr study, coniposeetl of 117 1)oll \vee\-il cohorts from ovenvintering hahitiits in the Rolling Plains of Texas, sho\vetl tliiit o\wvintering sitnii.orsliip and spring/s~~ninier emergence were inRi,mced by tlie daiy of tlie !.ear (Dol') wlien tlle wveekils entered oveniintering habitat the nniount of rainfiill, and 1ial)it;it trniperiitiires experienced by the weevils during cliupaiise. The e d i e r tlie date that IveeLils entered oveiwin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…2003. c of DD would require intimate knowledge of overwintering habitat and insulation, and ambient air temperatures overestimate positive DD by 6.5Ð15.7% (Parajulee et al 1997). Stone et al (1990) reported that, over a 7-yr study, the variation in emergence patterns can be Ͼ30 d. Although Parajulee et al (2001) developed a model for boll weevil survivorship on the Rolling Plains, overwintering habitats, food sources (Chandler and Wright 1991), the timing of weevil entry into overwintering habitat (Sterling 1971, Wade and, the date at which to begin calculating DD (Parajulee et al 1996), and the relative incidence of diapause, among other conceivable parameters, would differ in subtropical and tropical conditions where boll weevils are active and reproducing year-round (Guerra et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…2003. c of DD would require intimate knowledge of overwintering habitat and insulation, and ambient air temperatures overestimate positive DD by 6.5Ð15.7% (Parajulee et al 1997). Stone et al (1990) reported that, over a 7-yr study, the variation in emergence patterns can be Ͼ30 d. Although Parajulee et al (2001) developed a model for boll weevil survivorship on the Rolling Plains, overwintering habitats, food sources (Chandler and Wright 1991), the timing of weevil entry into overwintering habitat (Sterling 1971, Wade and, the date at which to begin calculating DD (Parajulee et al 1996), and the relative incidence of diapause, among other conceivable parameters, would differ in subtropical and tropical conditions where boll weevils are active and reproducing year-round (Guerra et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Low winter temperatures in most of the boll weevilÕs distribution in the United States cause substantial mortality in overwintering populations (Stone et al 1990, Parajulee et al 1996 which has assisted control programs to eradicate or suppress boll weevil infestations (Smith 1998). The Lower Rio Grande Valley of Texas, however, is a subtropical region of the United States with active, breeding boll weevil populations year-round (Guerra et al 1982, Summy et al 1988).…”
mentioning
confidence: 99%
“…Boll weevils move in the spring from overwintering habitats to young squaring cotton (Smith et al 1965, White andRummel 1978) in response to the cotton plant volatiles, including ethylene (Duffey and Powell 1979), and aggregation pheromone from boll weevils already in the Þeld (Parajulee and Slosser 2001). After overwintering mortality caused by low temperatures and reduction of food (Parajulee et al 1996), boll weevil populations are sparse.…”
Section: Differences In Mean (؎ Se) Percentage Variation Between Prmentioning
confidence: 99%
“…Low winter temperatures in most of the boll weevilÕs distribution in the United States cause mortality in overwintering populations (Stone et al 1990, Parajulee et al 1996 and this mortality has assisted control programs to eradicate or suppress boll weevil infestations (Smith 1998). The Texas Lower Rio Grande Valley, however, is a unique subtropical region of the United States that supports active, breeding boll weevil populations year round , Summy et al 1988) despite mandatory cotton stalk destruction before 1 September and prohibition on planting until 1 February (Texas Department of Agriculture 1998).…”
mentioning
confidence: 99%